HIV infection en route to endogenization: two cases. (18th December 2014) - Colson, P.; Ravaux, I.; Tamalet, C.; Glazunova, O.; Baptiste, E.; Chabriere, E.; Wiedemann, A.; Lacabaratz, C.; Chefrour, M.; Picard, C.; Stein, A.; Levy, Y.; et al.
Abstract The long‐term spontaneous evolution of humans and the human immunodeficiency virus (HIV) is not well characterized; many vertebrate species, including humans, exhibit remnants of other retroviruses in their genomes that question such possible endogenization of HIV. We investigated two HIV‐infected patients with no HIV‐related disease and no detection with routine tests of plasma HIV RNA or cell‐associated HIV DNA. We used Sanger and deep sequencing to retrieve HIV DNA sequences integrated in the human genome and tested the host humoral and cellular immune responses. We noticed that viruses from both patients were inactivated by the high prevalence of the transformation of tryptophan codons into stop codons (25% overall (3–100% per gene) and 24% overall (0–50% per gene)). In contrast, the humoral and/or cellular responses were strong for one patient and moderate for the other, indicating that a productive infection occurred at one stage of the infection. We speculate that the stimulation of APOBEC, the enzyme group that exchanges G for A in viral nucleic acids and is usually inhibited by the HIV protein Vif, has been amplified and made effective from the initial stage of the infection. Furthermore, we propose that a cure for HIV may occur through HIV endogenization in humans, as observed for many other retroviruses in mammals, rather than clearance of all traces of HIV from human cells, which defines viral eradication.